Coming of post-industrial society A venture in social forecasting - Bell, Daniel (London, 1974)
In 1976, Daniel Bell's historical work predicted a vastly different society developing$1 (Bone that will rely on the (3z(Beconomics of information(3y (Brather than the (3z(Beconomics of goods.(3y (BBell argued that the new society would not displace the older one but rather overlie some of the previous layers just as the industrial society did not completely eradicate the agrarian sectors of our society. The post-industrial society's dimensions would include the spread of a knowledge class, the change from goods to services and the role of women. All of these would be dependent on the expansion of services in the economic sector and an increasing dependence on science as the means of innovating and organizing technological change.Bell prophetically stated in The Coming of the Post-Industrial Society that we should expect (3z$1! = (Bnew premises and new powers, new constraints and new questions$1 (Bwith the difference that these are now on a scale that had never been previously imagined in world history.(3ys
Keywords: Societies